Nova Scotia Lost and Found:: The Acadian Boundary Negotiation and Imperial Envisioning, 1750-1755 - Lennox, Jeffers (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2011)
Abstract The Acadian boundary negotiations (1750-1755) marked a transition in the use of geography as an imperial tool. The discussions followed a two-step process: appointed commissioners representing Britain and France pored over old maps and geographic tracts but were unable to identify the most "ancient" Acadian boundary; direct diplomatic discussions then used cartography in an attempt to establish mutually agreeable limits in the northeast. These debates were shaped by Atlantic connections and competing Euro-Aboriginal claims to sovereignty. In lieu of material power on the ground, geography was used as a multi-faceted tool to address overlapping territories and the threat of war.